Etude de la génétique des populations du daltonisme chez les étudiants de l’université Abdelhamid Ibn Badis de Mostaganem - BENBERNOU, Nour El Houda Lalia (My University, 2025)
Color blindness is a congenital anomaly of color vision, generally linked to the X chromosome, and transmitted in a recessive mode. It results from mutations in the OPN1LW and OPN1MW genes, which code for red- and green-sensitive cone opsins, respectively, and can have a significant impact on daily life and professional performance. The aim of this study was to determine the prevalence of color blindness, and its gender distribution, and to test its fit to the Hardy-Weinberg model, in the student population of the Abdelhamid Ibn Badis University of Mostaganem. A cross-sectional study was carried out on 770 students from Mostaganem (338 men and 432 women), with a mean age of 21.36 ± 3.46 years, with the majority aged between 20 and 22. The results showed an overall prevalence of color blindness of 2.7%, including 5% in men and 0.93% in women, with a M/F color blindness sex ratio of 4.25. Only 4.42% of respondents said they had ever had a screening test. Students were unaware of the existence of color blindness in their families. Evaluation of the Hardy-Weinberg equilibrium showed a significant imbalance (χ² = 7.91 > 3.84), indicating that the observed genotype frequencies deviate from expected frequencies, probably due to inbreeding in the population, but not ruling out other evolutionary factors, such as migration or selection. Finally, this study constitutes the first local survey in this region, which will provide an original and valuable database that can serve as a reference for future research on a larger scale.
Keywords: colour blindness, prevalence, population genetics, Hardy-Weinberg equilibrium